2014
DOI: 10.1530/erc-14-0448
|View full text |Cite
|
Sign up to set email alerts
|

The new biology of estrogen-induced apoptosis applied to treat and prevent breast cancer

Abstract: The successful use of high dose synthetic estrogens to treat post-menopausal metastatic breast cancer, is the first effective “chemical therapy” proven in clinical trial to treat any cancer. This review documents the clinical use of estrogen for breast cancer treatment or estrogen replacement therapy (ERT) for postmenopausal hysterectomized women which can either result in breast cancer cell growth or breast cancer regression. This has remained a paradox since the 1950s until the discovery of the new biology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 185 publications
3
100
0
Order By: Relevance
“…This new biology of E 2 -induced apoptosis has been successfully used in clinical trials (7, 8). In the past, we have focused on the investigation of apoptosis-related signal pathways, genes, and cytoplasm organelles’ stress induced by E 2 in long-term E 2 -deprived breast cancer cells (5, 12, 13, 14, 23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new biology of E 2 -induced apoptosis has been successfully used in clinical trials (7, 8). In the past, we have focused on the investigation of apoptosis-related signal pathways, genes, and cytoplasm organelles’ stress induced by E 2 in long-term E 2 -deprived breast cancer cells (5, 12, 13, 14, 23).…”
Section: Discussionmentioning
confidence: 99%
“…However, acquired resistance to anti-estrogen therapies is still a challenge in the clinic. Laboratory findings that re-transplantation of tamoxifen-stimulated tumors into successive generations of athymic mice over 5 years results in the selection of a resistant tumor cell population that is killed by physiological levels of E 2 (2, 3), has resulted in the new biology of E 2 -induced apoptosis (47). Indeed, E 2 -induced apoptosis has been used successfully to treat breast cancer after the failure of AI therapy (8) and to explain the action of E 2 replacement therapy for postmenopausal women in their 60s having a lower incidence of breast cancer and mortality (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Hormone replacement therapy (HRP) was once widely used to ameliorate and prevent postmenopausal symptoms, including VMS and osteoporosis. However, its use has drastically declined since a report by the Women's Health Initiative (WHI) showed that HRP increases the risk of strokes, breast cancer, and pulmonary embolism (16)(17)(18)(19) (2,20). Recently, another estrogenic SERM, ospemifene, was approved by the US Food and Drug Administration for dyspareunia associated with vulvar and vaginal atrophy and menopause (21).…”
Section: Introductionmentioning
confidence: 99%
“…This is a demonstration of the consistent “carry over protective effect” of long term estrogen deprivation (LTED) therapies used to treat or prevent breast cancer (4). Since tamoxifen is not itself a cytotoxic agent, it is proposed that breast tumor cells with acquired resistance to LTED do not grow with estrogen but are killed by a woman’s own estrogen that induces apoptosis (5). …”
mentioning
confidence: 99%